Neuroobrazowanie. Przegląd krytyki fMRI = Neuroimaging. Review of critique of fMRI - Woźny, Michał (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The methods of neuroimaging are imperfect, but still can be useful. There are many controversies about fMRI data analysis and meaning of neuroimages themselves. The critique of neuroimaging spotlights various problems: possible statistical misinterpretations (like multiple comparisons), overestimate outcome of research, lack of knowledge about correlation between BOLD parameter and neural activity or biased hypothesis implicated by method. The critique of neuroimaging offers us a key to understand what do neuroimages really show.
Keywords: fMRI; neuroobrazowanie; błąd porównań wielokrotnych; BOLD (parametr); neuroimaging; multiple comparisons; BOLD (parameter)